Peran Perempuan dalam Mewujudkan Keluarga Sejahtera Menurut Perspektif Ekonomi Islam (Studi Kasus Perempuan Pedagang Kaki Lima di Simpang Tugu Tigo Baleh, Kelurahan Pakan Labuah, Kota Bukittinggi) - Zuwardi Zuwardi (HUMANISMA : Journal of Gender Studies, 2020)
Along with the development of the times of course the needs of society increase from year to year. Unlimited human needs, with limited availability of resources. Making women also play a role in meeting the needs of families in an effort to realize a prosperous family. This research was conducted to provide an overview of the role of women in realizing a prosperous family from the perspective of Islamic economics. Research conducted at the Tigo Tigo Baleh Intersection, Pakan Labuah Village, Bukittinggi City uses a qualitative descriptive approach with data obtained from primary and secondary data. The results of this study conclude that in Islamic sharia, to make a living is the duty of the husband. The wife's only obligation is as a housewife who educates children and serves her husband. But it is not forbidden when the wife helps find a living for the family. According to an interviewee at the interview, stated that they women do their activities as traders is to help their husbands in meeting family needs, as well as channeling the hobby of trade that has been buried because only become housewives. This research also provides understanding to women in order to know their rights and obligations in the household, the urgency of how Muslim women who should carry out their daily activities become housewives as well as traders in accordance with the recommendations in their Islamic Syariah.